Photodynamic therapy in a pleural cavity using monte carlo simulations with 2D/3D Graphical Visualization - Beeson K; Parilov E; Mary Potasek; Zhu T; Sun H; Sourvanos D (Global Journal of Cancer Therapy - Peertechz Publications, 2022)
Cancer therapy using Photodynamic Therapy (PDT) has been investigated for some time [1,2] and now it is a growing area of interest in clinical trials [3]. Monte Carlo (MC) simulations were used for early laboratory studies [4,5] for analysis in PDT. Various improvements in the MC method have advanced the field in recent years.